UJI TAPIS ISOLAT KHAMIR FILOSFER SEBAGAI AGENS BIOKONTROL PATOGEN ANTRAKNOSA PADA PISANG, Colletotrichum musae (Berk. dan Curt.) Arx. - Kurnia, Lulu; Rianto, Fadjar; Syahputra, Edy (Jurnal Sains Mahasiswa Pertanian, 2018)
ABSTRACTColletotrichum musae (Berk and Curt.) Arx. is a pathogen that causes anthracnose disease in bananas. Biological control is an alternative because it is friendly to the environment and reduces the negative impact of synthetic pesticides. The objective of this study was to obtain yeast isolates from bananas potentially used as biocontrol agents. The research was conducted at the Laboratory of Faculty of Agriculture Faculty of University of Tanjungpura Pontianak from September 2017 to February 2018. All the obtained yeast isolates were tested as antagonistic potential against C. musae through dual culture method and viability test of conidia C. musae. The hypovirulent test of yeast isolates that have potential as biocontrol agents are carried out on cucumber. The isolation result obtained 9 isolates of yeast. Based on antagonistic test, yeast isolates had inhibition between 53,42-78,67%. Viability test of conidia C. musae on media that has been shed in yeast cells as much as 106 cells/mL one day earlier showed that conidia still germinate 97.5-100%. Calculation of Severity Index of Disease in hypovirulent test for all isolates of yeast showed 0%. Keywords: antagonist, Colletotrichum musae, hypovirulen, spore germination, yeast